Das Alter einiger Dünen an der oberen Ems - Hambloch, Hermann (ERDKUNDE, 1958)
At the upper Ems river, superimposed on the sands of the low terrace, wide, dome-shaped dunes are found on the left bank, and high, hilly dunes on the right bank. On the basis of soil profiles, comparative analysis of grain sizes and archaeological finds it has been shown that the high dunes possess old cores of little height which were formed during the late glacial period. The layers on top, which in parts amount to some metres in thickness, were deposited during the Sub-Boreal and Sub-Atlantic period, most likely as a result of the earliest clearings when settlement began to occupy the edges of the terraces. Westerly and south-westerly winds have built up the hilly dunes with sand from the forest free places on the left bank and the floodplain; the stratification of the eolian deposits is very clearly recognisable. It has so far, however, not been possible to establish a parallelism between this sequence of finer and coarser sands with particular periods.